Computational fluid dynamics simulation of ethanol steam reforming in catalytic wall microchannels - Uriz, I. (2011)
A three-dimensional computational fluid dynamics (CFD) simulation study of the ethanol steam reforming (ESR) in microreactors with square channels has been carried out. A phenomenological kinetic model describing the ESR on a Co3O4-ZnO catalyst has been established and implemented in the CFD codes. This model includes the ethanol dehydrogenation to acetaldehyde, ethanol decomposition to CO and CH4, acetaldehyde steam reforming to H2 and CO2 and water-gas shift as the reactions describing the catalyst behavior. The very different thermal effects and apparent activation energies of these reactions allow interpreting the influence of the main operating parameters on the microreactors performance. The high activation energy and relatively low energy demand of the ethanol decomposition limit the production of hydrogen at high temperatures and space velocities (up to 70,000h-1) at yields of the order of 70%, that is, 4.2mol of H2 per mol of ethanol fed into the reactor. Another issue is the presence of significant CO contents in the reformate stream. This can be partially solved by increasing the catalyst loading which leads to a lower temperature and then an improved selectivity to ethanol dehydrogenation and acetaldehyde reforming. The microchannel characteristic size in the 0.10-0.70mm range has a strong influence on the microreactor performance that is mainly governed by the surface area-to-volume ratio. For the smallest sizes considered in this study (0.10 and 0.35mm) it has been found that the flow of the gases is nearly isothermal.